2015
DOI: 10.3906/tar-1406-85
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of azadirachtin application to soil on ureaseactivity and its kinetic parameters

Abstract: An ideal pesticide should be toxic only to the target organism and biodegradable, and its residue should not affect nontarget surfaces (Chowdhury et al., 2008). One such ideal alternative is the use of natural plant products that have pesticidal activity, such as azadirachtin (Akça et al., 2005). Azadirachtin possesses insecticidal activity against many economically important insect pests such as Helicoverpa armigera, Spodoptera litura, Plutella xylostella, Sitophilus oryzae, Sitophilus zeamis, Earis vitella, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…A high K m value indicates a weak binding affinity between the ES complex, while low K m demonstrates a strong binding. This finding is in line with that by Kizilkaya et al (2015) and Mathialagan et al (2019), which demonstrated that urease inhibitors applied with urea increased K m and retarded hydrolysis reaction. Meanwhile, V max reveals the catalytic efficiency of the enzyme by measuring the number of substrate molecules converted into products per unit time (Berg et al 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A high K m value indicates a weak binding affinity between the ES complex, while low K m demonstrates a strong binding. This finding is in line with that by Kizilkaya et al (2015) and Mathialagan et al (2019), which demonstrated that urease inhibitors applied with urea increased K m and retarded hydrolysis reaction. Meanwhile, V max reveals the catalytic efficiency of the enzyme by measuring the number of substrate molecules converted into products per unit time (Berg et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…It also works as an indicator to measure the speed of the enzymatic process in the soil. The lower the value, the slower the process (Kizilkaya et al 2015). Thus, a low V max compared with the control in the present study shows that less product was formed, which possibly occurs due to the formation of an enzyme-inhibitor complex that retards the formation and dissociation of the ES complex (Juan et al 2010;Lai and Tabatabai 1992).…”
Section: Discussionmentioning
confidence: 52%
“…The stimulatory effects of neem leaf extract on urea hydrolysis were found to be in line with the former studies of Mohanty et al (2008), Kizilkaya et al (2015), and Sridharan et al (2017). Urea hydrolysis stimulation was explained by Kizilkaya et al (2015), who stated that neem extract acted as a substrate providing C, N, and energy for soil microorganisms. This mechanism was supported by the significant increases in microbial biomass C in all neem extract rates, except Neem1 at 10 DAI (Fig.…”
Section: Urea Hydrolysissupporting
confidence: 85%
“…Pesticides may affect soil enzymes acting as alternative substrate. However, azadirachtin – the active ingredient of neem – showed opposite results, increasing urease activity because it acted as a source of energy for microorganisms instead of a urease inhibitor [19] , although neem has been recommended for addition to urea in India [21] .…”
Section: Mechanism Of Action Of Urease Inhibitorsmentioning
confidence: 99%
“…Neem also exhibits other properties of agronomic interest such as nitrification inhibition and pesticide effect [16] . The effect of neem coated urea to reduce urease activity has been demonstrated [17] but some studies noted that neem, or one of its active ingredients – azadirachtin – seems to stimulate urease activity [18] , [19] . Neem has more potential as a nitrification inhibitor [18] , [20] and for this reason all urea used in India since 2015 is mandatorily coated with neem [21] .…”
Section: Introductionmentioning
confidence: 99%